1997
DOI: 10.1093/cercor/7.3.268
|View full text |Cite
|
Sign up to set email alerts
|

Selective aging of the human cerebral cortex observed in vivo: differential vulnerability of the prefrontal gray matter

Abstract: In a prospective cross-sectional study, we used computerized volumetry of magnetic resonance images to examine the patterns of brain aging in 148 healthy volunteers. The most substantial age-related decline was found in the volume of the prefrontal gray matter. Smaller age-related differences were observed in the volume of the fusiform, inferior temporal and superior parietal cortices. The effects of age on the hippocampal formation, the postcentral gyrus, prefrontal white matter and superior parietal white ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

99
851
17
21

Year Published

1998
1998
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,152 publications
(988 citation statements)
references
References 87 publications
99
851
17
21
Order By: Relevance
“…Several studies have shown 113 that the volume of the hippocampal formation is larger in men than in women. 1,72,114 In developing children aged 4-18 years, the hippocampus increases with age. 115 In men, the hippocampus declines with age, starting in the third life decade.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown 113 that the volume of the hippocampal formation is larger in men than in women. 1,72,114 In developing children aged 4-18 years, the hippocampus increases with age. 115 In men, the hippocampus declines with age, starting in the third life decade.…”
Section: Discussionmentioning
confidence: 99%
“…Volumes of hippocampus and parahippocampal gyrus were found to decline significantly with age. Several authors have reported similar age-related volume decreases in these regions [8,9,12,18,26,31]. However, other authors have failed to find such a decline in medial temporal lobe volumes [24,31,37].…”
Section: Normal Brain Agingmentioning
confidence: 91%
“…Several authors have reported similar age-related volume decreases in these regions [8,9,12,18,26,31]. However, other authors have failed to find such a decline in medial temporal lobe volumes [24,31,37]. Linear increases with advancing age were found for the volume of the third ventricle (taken as an index for atrophy of the dorsomedial thalamus [19]).…”
Section: Normal Brain Agingmentioning
confidence: 92%
See 1 more Smart Citation
“…While the involvement of prefrontal cortex in Major Depressive Disorder has been well documented (Mayberg et al, 1994;Bench et al, 1992), it is an especially salient issue in geriatric depression because this region of the brain is associated with disproportionate age-related decline (Raz et al, 1997). In particular, MRI findings of deep white matter hyperintensities involving frontal-subcortical pathways are associated with both chronicity and cognitive impairment in late-life depression (Krishnan et al, 1998;Steffens et al, 2000;Lesser et al, 1996).…”
Section: Introductionmentioning
confidence: 99%